Divulgação cientifica em saúde: contribuições para a formação acadêmica e letramento científico - CARVALHO, Josilayne Patricia Ramos (2021)
Scientific communication is a didactic and accessible strategy to share academic knowledge with to general population and promotes scientific literacy as a tool for social inclusion. At the same time, is a training strategy for students in health science courses. The main aim of this study was to investigate the scientific communication’ contributions for professional education in health sciences and population’ science literacy. This is a qualitative study, based on a narrative approach. Banners and experiments were used as motivators for the discussion and Neurosciences’ concept explanations and demystification of neuromyths. People of all ages and social classes who were at the university were welcome to participated. Based on the discursive textual analysis, the categories were analyzed: i) Critical and reflective positioning; ii) motivated personal experiences; iii) reflections on habits and potential changes; iv) collaborative and integrative personal and professional learning. We concluded that scientific communication was effective to clarified neuromyths, improve autonomy and adherence on healthy lifestyle, as well as for the academic and professional education of the students involved.